The Suppressive Effects of the Petroleum Ether Fraction from Atractylodes lancea (Thunb.) DC. On a Collagen‐Induced Arthritis Model. (3rd July 2016) - Liu, Renping; Tao, Enwei; Yu, Shuwen; Liu, Bo; Dai, Lingman; Yu, Liangyu; Xiong, Yifeng; Fu, Ruijun; Lei, Lang; Lai, Xiaoping
Abstract : In Chinese traditional medicine, the rhizome of Atractylodes lancea (Thunb.) DC. ( A .  lancea ) is used extensively for the treatment of several diseases such as rheumatic diseases, but its actions on rheumatoid arthritis have not been clarified. The purpose of this article was to investigate the pharmacological effect of an A .  lancea rhizome extract on collagen‐induced arthritis (CIA) in rats. The CIA model was induced by the injection of bovine type II collagen. The rats were orally administered the petroleum ether (PE) fraction of the A .  lancea rhizome (0.82 and 1.64 mg/kg), methotrexate (0.3 mg/kg body weight), or a vehicle from day 7 to day 15 after the model was established. The histological examination and radiological observation showed that the PE fraction significantly reduced the inflammatory responses and collagen loss in the joints of the rats with CIA. The PE fraction inhibited the production of tumor necrosis factor‐α, interleukin (IL)‐1β, IL‐17, and IL‐6 in the sera. Moreover, the treatment with the PE fraction in vivo was able to reduce the level of Beclin 1 protein in the synovial tissue of the rats. These results highlight the antiarthritic potential of the PE fraction of the A .  lancea rhizome and provide further evidence of the involvement of Beclin 1 inhibition in the effects of the PE fraction of the A .  lancea rhizome. Copyright © 2016 John Wiley & Sons, Ltd.